Government Language and U.S. Health Care - Wilson, Asa; Gray, Natallia (Archives of Business Research, 2025)
Context: Concerns about the use of language as a reliable communication medium are identified. This review is a foundation for analyzing federal language regarding the healthcare industry and the efficacy of this high-cost paradoxical system. An argument is developed that government language about U.S. health care has unique, predictable features. Methods: This language-use style is exemplified using authoritative federal sources such as Executive Orders, Federal Register rulemaking communications, and agency administrative rule promulgations. Findings: Six distinct language attributes are identified and discussed. Conclusion: This federal language style is also a harbinger of future federal involvement in U.S. health care.